Methodology on the trend of underlying shariah contracts and legal disputes of decided Islamic banking cases in Malaysia - Ahmad Pauzi, Nur Faakihin; Hassan, Rusni; Salleh, Safinar; Salman, Syed Ahmed (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The general reflection of certainty and predictability in the decisions of the courts could be traced from the trend of decided Islamic Banking cases itself. Some studies highlighted the trend in decided Islamic Banking cases but not in detail, with a limited scope of discussion and did not cover the current and the latest decided cases. The objective of this paper is to provide a comprehensive analysis on the decided Islamic Banking cases in Malaysia of year 1987 to 2018 in order to find out the trend of underlying Shariah contract and legal disputes. The method employed in this study is the legal research through the analysis decided Islamic Banking cases in Malaysia. This paper highlights the underlying Shariah contracts that attract numerous judicial consideration and legal disputes in different phases of development in Islamic Banking cases. The diversification underlying Shariah contract and the complexity of legal issues could be traced in the more recent decided Islamic Banking cases. Moreover, the findings contribute to the enhancement of disputes resolution outcomes through court process and improvise the Shariah compliance and legal risk management of Islamic Banking Institutions